Sillenium Optical dan Rakan-Rakan / Muhammad Al Yufizli Mazelan ... [et al.] - Mazelan, Muhammad Al Yufizli; Abd Jalil, Muhammad Arib; Jamal Abd Nasir, Ahmad Jihbaz Mukhlis; Ismail, Amir Qair; Joh, Imran (Faculty of Architecture, Planning and Surveying, 2005)
SILLENIUM OPTICAL provides a service to sale several of spectacles and service. Our business will developed under five members as partnerships. The business that we chose in this plan is setting up a Sillenium Optical. We would provide both commercial and sell service to our pupils use the speck. Our coverage of services includes check or inspection eye, measure lenses with frame, sell frame and lenses. Our dedicated and full cooperated members will do anything without regrets to make sure that our business will success. There for we have choose an ideal place to start our business.